Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit